Księga Sofoniasza w Qumran - Parchem, Marek (Collectanea Theologica, 2018)
Like other prophetic texts, the Book of Zephaniah enjoyed popularity and recognition by the members of the Qumran community. This is testified to by five biblical manuscripts of that book, four in Hebrew (4Q77-78, 4Q82, Mur 88) and one in Greek (8Hev 1), quotations in the Rule of the Community (1QS 5:11 = Zeph 1:6) and in the Exposition on the Patriarchs (4Q464 frg. 4, col. 3, line 9 = Zeph 3:9), direct allusions in the Rule of the Community (1QS 10:22; par. 4Q260 frg. 1, col. 3, line 3 = Zeph 3:13), allusions in the Thanksgiving Scroll (1QH 13:32 and 17:6 = Zeph 1:15), in the Paraphrase of the Books of the Kings (4Q382 frg. 9, line 4 = Zeph 1:5), in the Words of the Lights (4Q504 frg. 1-2, col. 5, lines 5-6 = Zeph 1:18; 3:6.8), as well as by its existence in the form of two scrolls as the Pesher Zephaniah (1Q15; 4Q170). Even though the extant texts of the Pesher Zephaniah are highly fragmentary and do not have much content, the very fact of their existence proves that the biblical Book of Zephaniah was the subject of intense studies carried out by the members of the community, and that its text served as a source of commentary.